Organic chemistry : an introductory course - Lowther, Harold (Commonwealth and international library. Chemistry division, 1964)
Organic Chemistry: An Introductory Course is an introductory textbook that covers the significant developments in organic chemistry. This book is composed of 20 chapters that particularly focus on the basic, physico-chemical principles and reactions. The first 10 chapters explore the classification, physico-chemical properties, analysis, and reactions of numerous organic compounds, including aliphatic compounds, aldehydes, alcohols, esters, ethers, and acid derivatives. The subsequent three chapters describe the optical activity, stereoisomerism, biological significance, and industrial applica.